Dux cluster duplication ensures full activation of totipotent genes - Meiqi Lin; Zeling Du; Dan Guo; Yiran Zhang; Jiameng Dan (Proceedings of the National Academy of Sciences, 2025)
Zygotic genome activation (ZGA) confers to the mouse two-cell (2C) embryo a unique transcriptional profile characterized by transient up-regulation of many totipotency-related genes and MERVL retrotransposons. Intriguingly, those genes are duplicated and clustered in the genome during evolution, including Dux cluster, Obox, and Zscan4 family members in mice. However, the contribution and biological significance of the totipotency-related gene duplication events in early embryo development remain poorly understood. Here, we focus on Dux cluster, the master regulator of ZGA that is necessary and sufficient for the induction of 2C-like cells and activation of totipotency-related genes in mouse embryonic stem cells (mESCs). By reducing Dux gene copies from 31 to 0 or 1 through CRISPR-Cas9 technology, we generate Dux -KO and Dux (n = 1) mESC lines, respectively. We uncover that the totipotency-related gene transcriptional profile is awakened to a much lesser extent in Dux (n = 1) mESCs compared to wild type mESCs following global DNA demethylation reprogramming or induction of DNA damage, mimicking the intrinsic events in preimplantation development. Together, Dux cluster duplication is critically required for full activation of ZGA transcripts.